Superior response inhibition to high-calorie foods in adolescents with anorexia nervosa. (January 2020) - Weinbach, Noam; Lock, James; Bohon, Cara
Abstract: Anorexia nervosa (AN) is a severe eating disorder that is characterized by significant weight loss as a result of self-starvation. Little is known about the mechanisms that allow these patients to endure self-starvation for long periods of time. It has been suggested that the neurocognitive mechanism responsible for stopping inappropriate actions (i.e., response inhibition) may contribute to this process. However, empirical evidence to support this notion is lacking. The goal of the current study was to assess if exposure to high-calorie food stimuli may trigger response inhibition to a greater extent in adolescents with AN compared to healthy adolescents. Thirty adolescents with restrictive type AN (AN-R) and 30 healthy adolescents completed a food-stop signal task wherein their ability to inhibit prepotent responses was assessed following exposure to high- and low-calorie food images. The results revealed superior ability of adolescents with AN-R to inhibit actions following exposure to high-calorie food images compared with controls. No such difference was found between the groups following exposure to low-calorie foods. The results indicate that high-calorie foods automatically trigger stronger activation of response inhibition in adolescents with AN compared to healthy adolescents. Such activation is likely a unique feature of AN that potentially contributes to patients' ability to severely restrict eating. Highlights: Response inhibition (RI) is the mechanism responsible for inhibiting undesired actions. Superior RI to high-calorie foods may maintain restricted eating in anorexia nervosa (AN). The study assessed RI to high- and low-calorie food images in adolescents with AN. High-calorie food images triggered stronger activation of RI in AN.